PENINGKATAN HASIL BELAJAR SISWA DENGAN PENERAPAN MODEL PEMBELAJARAN LANGSUNG PADA MATERI POKOK SIKLUS AKUNTANSI PERUSAHAAN JASA - Nurul Ahadiyah, (Pendidikan Ekonomi, 2010)
The study aims to examine how the direct instruction model was used to increase the students achievement. This study is a classroom action research which consists of three cycles. The subjects were the eleventh graders of social science 3 at SMA Negeri 1 Ngoro.  The findings reveal that the students and teachers learning activities are good and the students learning mastery increase in the three cycles. Moreover, most of students agreed on the use of direct instruction.